Recurrence risk of congenital malformations in infants exposed to antiepileptic drugs in utero. Issue 1 (21st November 2012) - Campbell, Ellen; Devenney, Emma; Morrow, Jim; Russell, Aline; Smithson, William Henry; Parsons, Linda; Robertson, Iain; Irwin, Beth; Morrison, Patrick J.; Hunt, Stephen; Craig, John
Summary Purpose: Use of antiepileptic drugs in pregnancy is associated with congenital malformations and developmental delay. Previous studies have suggested that women who have had one child with a congenital malformation are at increased risk of having other children with malformations. We sought to confirm the magnitude of risk in a large cohort drawn from the United Kingdom Epilepsy and Pregnancy Register. Methods: The United Kingdom Epilepsy and Pregnancy Register is a prospective, observational registration and follow‐up study set up to determine the relative safety of antiepileptic drugs in pregnancy. We have extracted data for those women who prospectively registered more than one pregnancy and calculated the recurrence risks for fetal malformations. Key Findings: Outcome data were available for 1, 534 pregnancies born to 719 mothers. For women whose first child had a congenital malformation there was a 16.8% risk of having another child with a congenital malformation, compared with 9.8% for women whose first child did not have a malformation (relative risk 1.73, 95% confidence interval [CI] 1.01–2.96). The risk for recurrence was 50% for women who had had two previous children with a congenital malformation. There was a trend toward a higher risk for recurrent malformations in pregnancies exposed to valproate (21.9%, relative risk 1.47, 95% CI 0.68–3.20) and topiramate (50%, relative risk 4.50, 95% CI 0.97–20.82), but not for other drugs such as carbamazepine and lamotrigine. Recurrence risks were also higher for pregnancies exposed to polytherapy regimens and for those where the dose of antiepileptic drug treatment had been increased after the first pregnancy. Significance: Women who have had a child with a malformation are at increased risk of having other children with malformations. This is in keeping with previous reports that have suggested that genetic influences may be one of the factors determining the teratogenic risk of antiepileptic drugs.